TRADISI BHEN-GHIBEN PADA PERKAWINAN ADAT MADURA (STUDI KASUS DI KABUPATEN SUMENEP-MADURA) - Susantin, Jamiliya; Rijal, Syamsul (Jurnal TAMBORA, 2021)
The Ben-Ghiben tradition is the tradition of bringing items by the groom to the housefor the bride in the form of household items, namely cabinets, chairs, beds,and all kinds of kitchen utensils. The purpose of this study is toknow and analyze the Ben-Ghiben tradition of Madurese traditional marriage.The methodology is qualitative with research stages 1. observation,2. interviews and 3. documentation. For data analysis usingdescriptive-phenomelogical analysis. The result of the research is the tradition of marriage inMadura is different from the tradition of marriage in Java, if it adheres to Madurathe majority adhere to the matrilineal tradition, where husband and wife perform afterwardsmarriage is required to live in the wife's house. And the future husband brought Bhen-Gibhen (luggage in the form of cabinets, chairs, beds and home furnishingsother stairs). And the wife provides a house to live in.